DYNAMICS OF EARNING MANAGEMENT, TRANSFER PRICING, AND SALES GROWTH ON TAX AVOIDANCE: THE ROLE OF MANAGERIAL OWNERSHIP MODERATION - Paulus, Hendro; Deden Tarmidi (Jurnal Akuntansi Trisakti, 2025)
This research seeks to empirically investigate the effect of Earnings Management, transfer pricing, and sales growth on tax avoidance, with managerial ownership considered as a moderating variable. The study focuses on manufacturing firms listed on the Indonesia Stock Exchange during 2019–2023, selected through purposive sampling, resulting in 76 companies and 380 panel observations analyzed using EVIEWS 13. The findings reveal that among the three independent variables, only sales growth significantly influences tax avoidance, while Earnings Management and transfer pricing show no significant impact. Nevertheless, managerial ownership is found to moderate the relationship between Earnings Management, transfer pricing, and sales growth with tax avoidance. These insights are valuable for both investors and corporate managers in evaluating tax avoidance practices.